In‐person victimization, cyber victimization, and polyvictimization in relation to internalizing symptoms and self‐esteem in adolescents with attention‐deficit/hyperactivity disorder. (25th June 2021) - Fogleman, Nicholas D.; McQuade, Julia D.; Mehari, Krista R.; Becker, Stephen P.
Abstract: Background: There is mixed evidence for whether in‐person victimization and cyber victimization are differentially linked to internalizing symptoms and self‐esteem among adolescents with attention‐deficit/hyperactivity disorder (ADHD). The goals of the present study were to (1) evaluate in‐person victimization and cyber victimization in relation to internalizing symptoms (i.e., anxiety and depression) and self‐esteem and (2) examine differences in internalizing symptoms and self‐esteem between in‐person victimization, cyber victimization, and polyvictimization (i.e., both in‐person victimization and cyber victimization). Methods: Participants were 78 adolescents (ages 13–17 years) diagnosed with ADHD who completed ratings of in‐person victimization, cyber victimization, anxiety, depression, and self‐esteem. Parents completed ratings of their adolescent's anxiety and depression. Results: Adolescents with ADHD reported experiencing higher rates of in‐person victimization (64%) than cyber victimization (23%) in the last 30 days. In addition, 22% reported that they experienced polyvictimization. In‐person victimization was associated with higher adolescent‐reported anxiety symptoms, whereas cyber victimization was associated with higher parent‐reported depressive symptoms; both were associated with lower adolescent‐reported self‐esteem. Adolescents who reported polyvictimization reported the highest anxiety and depressive symptoms and the lowest self‐esteem. Conclusions: Approximately one quarter of adolescents with ADHD report experiencing polyvictimization in the past month. Findings indicate that in‐person victimization and cyber victimization are each uniquely associated with lower self‐esteem and differentially associated with co‐occurring internalizing symptoms among adolescents with ADHD. Polyvictimization is especially linked to higher internalizing symptoms and lower self‐esteem. Longitudinal studies are needed to better understand the directionality of these associations.